Evaluation of polymorphism in BCL-2, PD-1, and PD-L1 genes in myelodysplastic neoplasms - Bartłomiej Kuszczak; Piotr Łacina; Marta Dratwa-Kuźmin; Katarzyna Bogunia-Kubik; Tomasz Wróbel; Justyna Rybka (Acta Haematologica Polonica)
B-cell CLL/lymphoma 2 (BCL-2) family proteins regulate apoptosis, while programmed cell death protein 1 (PD-1) and programmed death-ligand 1 (PD-L1) act as negative regulators of the immune system. An association has been found between abnormalities in BCL-2 and PD-1/PD-L1 proteins and susceptibility to myelodysplastic neoplasms. The aim of this study was to assess polymorphisms in genes encoding BCL-2, PD-1, and PD-L1 and their impact on the clinical course of myelodysplastic neoplasms (MDS), treatment effectiveness and correlation with other prognostic factors in MDS. The study included 50 individuals with a median age of 70 who had been diagnosed with MDS. Genotyping for BCL2 (rs1564483, rs2279115), CD274 (rs2297136, rs4143815), and PDCD1 (rs10204525, rs2227981) was performed using LightSNiP assays. Real-time PCR reactions were conducted on a LightCycler 480 II device. Mann- Whitney U test and Fisher’s exact test were employed for analysis. Kaplan-Meier curves and the log-rank test were used for survival analysis. The analysis revealed that the BCL2 rs1564483 G allele is associated with better overall survival compared to patients with the BCL2 rs1564483 AA genotype (p = 0.037), and is more common in patients who achieve complete remission (CR) or partial remission (PR) after first-line treatment (regardless of the therapy used) (p = 0.021).